Challenges of imaging structure and function with MRI. - Turner, R. (IEEE Engineering in medicine and biology magazine)
Deals with current image reconstruction and processing issues in MRI for the study of tissue structure and function. In image reconstruction, the authors discuss the need for new algorithms that can produce high-resolution images with good signal-to-noise ratio from reduced amounts of data. In image processing, the authors describe outstanding problems in automatic image registration and segmentation